A Cross-Sectional Study of Labial Bone and Covering Soft Tissue in Maxillary Anterior Segment: A Dilemma in Orthodontics - Saeed Yousefzadeh; Maryam Johari; Sedigheh Sheikhzadeh; Sina Haghanifar; Hemmat Gholinia; Nazanin Arbabzadegan Hashemi (Hindawi Limited, 2021)
Purposes. The thickness of the buccal bone and its covering gingiva is pivotal in determining the prognosis of implant therapy as well as fixed orthodontic appliances, especially nonextraction treatments. The purpose of this study was to evaluate the buccal bone thickness and covering soft tissue in the maxillary anterior segment. Methods. This study measured the hard tissue thickness at 2 and 5 mm more apical from the crest and at the root apical apex, as well as the distance from the CEJ to the alveolar crest, using 80 CBCT images divided into three age groups. In addition, the distance from free gingiva to alveolar crest and from free gingiva to CEJ was measured. The acquired data then was analyzed using an ANOVA, t-test, and Pearson correlation to investigate any associations or statistically significant differences between parameters. Results. The highest mean soft tissue thickness at the 5 mm level was for central incisors and the least for canine. The highest mean thickness of soft tissue at the crest level and its 2 mm apical level was related to central incisors and the lowest mean thickness at these levels was related to canine. Analysis of hard tissue variables showed the lower thickness of hard tissue at higher ages compared to the young patients group, but the thickness of the soft tissue increases with age. Conclusion. The highest mean thickness of the buccal hard tissue in the maxillary anterior segment was in lateral and central incisors. Also, the most prominent thickness of the labial soft tissue was in the central and lateral incisors at levels close to the crest.